2010
DOI: 10.1161/atvbaha.109.197178
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Factor XIa as a New Approach to Anticoagulation

Abstract: Abstract-The dose-limiting issue with available anticoagulant therapies is bleeding. Is there an approach that could provide antithrombotic protection with reduced bleeding? One hypothesis is that targeting proteases upstream from the common pathway provides a reduction in thrombin sufficient to impede occlusive thrombosis yet allows enough thrombin generation to support hemostasis. The impairment of intrinsic coagulation by selective inhibition of factor XI (FXI) leaves the extrinsic and common pathways of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 50 publications
1
87
0
2
Order By: Relevance
“…High plasma fXI levels are associated with increased risks for arterial 42 and venous thrombosis 43 , and incidences of stroke 44 and deep venous thrombosis 45 are reduced in severe fXI deficiency. Inhibition of fIX activation by fXIa produces an antithrombotic effect in several species, 46 including primates, 12,21 supporting an important role for fXIa in thrombus formation in humans. Paradoxically, a link has been suggested between fXII deficiency and thrombosis dating back to the death of the first described fXII-deficient patient from a pulmonary embolism.…”
Section: Discussionmentioning
confidence: 93%
“…High plasma fXI levels are associated with increased risks for arterial 42 and venous thrombosis 43 , and incidences of stroke 44 and deep venous thrombosis 45 are reduced in severe fXI deficiency. Inhibition of fIX activation by fXIa produces an antithrombotic effect in several species, 46 including primates, 12,21 supporting an important role for fXIa in thrombus formation in humans. Paradoxically, a link has been suggested between fXII deficiency and thrombosis dating back to the death of the first described fXII-deficient patient from a pulmonary embolism.…”
Section: Discussionmentioning
confidence: 93%
“…This assumption is based on (1) the highest affinity for FXIa vs other coagulation factors, as calculated by SPR, ITC, and kinetics experiments; (2) the prolongation of the aPTT ex vivo without change in the PT; (3) the finding that salivary inhibitors targeting FXa (eg, tick anticoagulant peptide, antistasin, Lufaxin), 26,44 but not FIX(a) (eg, nitrophorin-2), 45 inhibit experimental thrombosis at concentrations that consistently promote bleeding; and (4) the emerging concept that FXIa plays a major role in thrombus formation in vivo but not for hemostasis. 11,46 Accordingly, interference with FXI(a) function through genetic deletion, 43,46 blockade with antibodies 9,10 or small-molecule inhibitors, 47 or by reduction of FXI synthesis with antisense oligonucleotides 48 results in inhibition of thrombosis with no bleeding phenotype. This profile, also observed here with Desmolaris, represents a novel antithrombotic strategy associated with potentially safe anticoagulation.…”
Section: Discussionmentioning
confidence: 99%
“…This profile, also observed here with Desmolaris, represents a novel antithrombotic strategy associated with potentially safe anticoagulation. 11,47 Nevertheless, Desmolaris may interfere with hemostasis at higher doses (.250 mg/kg), which is compatible with an anticoagulant targeting FXa. In fact, Desmolaris inhibits FXa-triggered paw edema in mice, an inflammatory event associated with PAR2 activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the cleaved light chain (FXIa) reduces the size of the clot and may lead to fewer bleeding side effects than when other coagulation factor isozymes are targeted. 6,7 In recent years, several studies of human factor XI have been reported on FXIa-specific inhibitors in order to replace the existing therapies. Previous studies have found that the basic P1group, such as benzamidine or guanidine, interacts with Asp189 in the S1 pocket of FXIa.…”
Section: Introductionmentioning
confidence: 99%